PROTOTYPE REGENERATOR OKSIGEN BERBASIS MIKROKONTROLER PADA KERETA JARAK JAUH - TEGUH ARIFIANTO; Faisal Ilham; Santi Tri Wijaya (STMIK YADIKA BANGIL, 2020)
Abstract: As is known on long-distance passenger trains there is only air conditioning as nothing produces oxygen. While in a closed room the change of air is needed in order to breathe enough oxygen. This is necessary so that the CO2 in the train is not inhaled by passengers in a long time and in large quantities. Please note that CO2 levels that are already classified as high in human health reach 1500 ppm. At that point humans began. If this happens it will certainly reduce the level of comfort of passengers traveling on the train. The manufacture of this tool uses sensors MQ-135 and MQ-2 as detectors of air quality controlled by Arduino Uno as the processor. The output from the previous process is the ozone generator which will produce oxygen and an air pump. Keyword : CO2, arduino uno, ozone generator